Sasanian Iran in the Context of Late Antiquity
1 online resource.
Keywords: This volume is a collection of papers on the various aspects of Sasanian world which were delivered at the University of Oxford in 2014. Eminent scholars in such fields as numismatics, history, art history, Pahlavi and Zoroastrian Studies provide important observations on the Sasanian Empire and its influence and contact with the neighboring civilizations, as well as the internal developments throughout the four centuries in which the Sasanians held power on the Iranian Plateau and beyond. This volume was previously published by the Jordan Center for Persian Studies, University of California - Irvine.